Hadrian's Judaean "Adventus coins": a question of perspective - Ben Zeʾev, Miryam Putsʹi (Journal of Jewish studies, 2025)
Hadrian's visit to Judaea was celebrated by the issue of coins, the so-called Adventus coins, which displayed the personification of the province of Judaea as a woman, standing opposite the emperor, in the act of sacrificing over an altar. Since traditional Jews not only did not sacrifice on pagan altars but considered this kind of sacrifice as a betrayal of the very core of their monotheistic heritage, some scholars interpret these coins as a provocation and a deliberate disregard of Jewish traditions. It is, however, a question of perspective, since the design is the same as that displayed on all the Adventus coins pertaining to the other provinces. It therefore appears that, at least from a Roman point of view, Hadrian's Judaean Adventus coins did not carry a particular political meaning'.